Bacterial flora of the appendix fossa in appendicitis and postoperative wound infection - Leigh, D. A. (1974)
Bacteria were isolated from 153 (47·5%) swabs of the appendix fossa in 322 patients undergoing appendicectomy. The commonest organism was Bacteroides species found in 78% of specimens. Other Gram-negative bacilli such as Klebsiella, or Enterobacter, and Esch. coli were present in 29 and 27% respectively. Gram-positive cocci were less frequently isolated. A positive culture was obtained more commonly in perforated appendicitis (79%) than where chronic fibrosis, lymphoid hyperplasia, or acute appendicitis was present or when the appendix was normal. Bacteroides was isolated twice as often in perforated appendicitis. The incidence of wound infection was 19% and varied according to the state of the appendix, being 63% in perforated appendicitis and 9·5% where lymphoid hyperplasia was present. Bacteroides was isolated from over 90% of the wound infections. In the patients with perforated appendicitis where effective chemotherapy was given the incidence of wound infection was 15% whereas in untreated or inappropriately treated patients it was over 50%. The isolation of bacteroides requires special precautions to be taken both in the collection of the specimen and laboratory culture. It is important that the chemotherapy of postappendicectomy infections include an antibiotic active against bacteroides.